CORE SELF EVALUATIONS, COPING STRATEGIES AND LIFE SATISFACTION AT PEDAGOGICAL FORMATION PROGRAM STUDENTS - Esin ÖZER (Fırat University, 2019)
In this study, it is aimed to determine whether core self evaluations and coping strategies predict life satisfaction of pedagogical formation program students or not. The pedagogical formation program was designed to give special subjects, teaching experiences to students who graduate or been a student different departments apart from faculty of education in order to gain the teaching knowledge and skills. The study group includes the pedagogical formation program students of Faculty of Education at Duzce University’s at first semestr of 2015--2016 Academic year. The study group contains the students with age ranges from 22-45, 49 of whom are males,137 of whom are females, 186 in total, selected with cluster sampling method randomly and participate in the study voluntarily. The Core -Self Evaluations Scale, Cope Inventory –Short Form, Satisfaction With Life Scale (SWLS) was used to collect data for the current study. In order to determine whether core self evaluations and coping strategies predict life satisfaction or not, regression analysis was conducted. The results of which indicate that Core Self Evaluations and coping styles have a significant predicting role on life satisfaction. Core Self Evaluations and Coping strategies clarify 28 % of variance in life satisfaction.Ranking of predicting variables on the life satisfaction according to their importance was firstly core self evaluations and then coping styles.